Population estimation and distribution of a benthic fish, Glossogobius sp., in a tin mine lake, the Mine Resort, Malaysia - Wong, I.L.L. (Universiti Putra Malaysia, 2015)
The Strip count method was used in the estimation of population and distribution of the gobiid, Glossogobius sp. in a tin mine lake. Counts were made by divers using SCUBA gear on 1 meter wide transects laid perpendicular on the bottom of the lake to the inshore fringe of the lake. A comparison was done between the shallow end and the deep end sites of the lake to see the influence of man`s activities on their population and distribution pattern. The distribution of the gobiid in relation to the depth and each site was conducted. Size class distribution of the gobiid in relation to depth and site was also determined.